VIABILITY AND PRODUCTION CALCIFYING BACTERIAL ENDOSPORE ON SAND-CEMENT CARRIER - Apriliani Devinta; Enny Zulaika (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Carbonatogenic bacteria have the ability to precipitate calcium carbonate (CaCO3) and many calcareous areas are found. Some of its species formed endosporas which resistant to harsh physical condition such as very alkaline pH. The objectives of this study were to obtain spore biomass and determine endosporas viability in tested carrier media such as sand-cement. The tested isolates were Bacillus JA1, JB3, SU1, AK4, Lysinibacillus JB2, and Sporosracina JA4. The production of endosporas was carried out on yeast urea broth with a temperature treatment of 70°C for 20 minutes. The formed endosporas were stored in carrier medium of sand, cement, and a mixture of cement sand. Spore viability was conducted using total plate count method. The results showed that all isolates were able to produce endosporas with the highest endosporas dry biomass is Bacillus AK4 which was 196 mg/L. After 2 hours of storage, endosporas were still able to grow by forming colonies on nutrient agar media.